Moving online - exploring the effects of online communication on social interactions. - Goh, Gloria Yu Yu. (2013)
Past studies show a mixture of responses to online communication, with some research indicating that online communication is detached from offline interactions. Other studies view the Internet as an alternative platform for communication, where online communication is viewed as a commitment of individuals to social interaction. This paper investigates the meanings individuals ascribe to the online platform of social media, and reveals that while online communication is rampant, it is unable to replace offline interactions. Adopting the symbolic interactionist approach, it is found that respondents in this research ascribe various meanings onto social media platforms that determine their usage patterns of such platforms. Findings reveal that respondents conscientiously manage their contacts online and social media is treated as a public space that restricts open sharing amongst online interactants. Additionally, respondents find online interaction on social media to lack a quality of communication that offline interaction provides.